2010
DOI: 10.3945/ajcn.2009.28761
|View full text |Cite
|
Sign up to set email alerts
|

HIV and hepatocellular and esophageal carcinomas related to consumption of mycotoxin-prone foods in sub-Saharan Africa

Abstract: HIV transmission frequency is positively associated with maize consumption in Africa. The relation between cancer and food suggests that fumonisin contamination rather than aflatoxin is the most likely factor in maize promoting HIV. Changes to the quality of maize may avoid up to 1,000,000 transmissions of HIV annually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 27 publications
1
55
0
1
Order By: Relevance
“…Further, it is a potent immunotoxic agent in animals and also changes T-cell phenotypes in humans, which may aggravate the burden of infectious diseases in the developing world (Williams et al 2004;Jiang et al 2005;Wild 2007). AF contamination is an important problem in relation to food quality/food safety in Africa as a result of poor production and storage practices for major staples of the African diet (Hell et al 2000;Williams et al 2004Williams et al , 2010Lewis et al 2005). Studies in Uganda indicate that AF exposure is broadly similar to that reported from other African countries (Kaaya & Warren 2005).…”
Section: Please Scroll Down For Arti Clesupporting
confidence: 49%
See 2 more Smart Citations
“…Further, it is a potent immunotoxic agent in animals and also changes T-cell phenotypes in humans, which may aggravate the burden of infectious diseases in the developing world (Williams et al 2004;Jiang et al 2005;Wild 2007). AF contamination is an important problem in relation to food quality/food safety in Africa as a result of poor production and storage practices for major staples of the African diet (Hell et al 2000;Williams et al 2004Williams et al , 2010Lewis et al 2005). Studies in Uganda indicate that AF exposure is broadly similar to that reported from other African countries (Kaaya & Warren 2005).…”
Section: Please Scroll Down For Arti Clesupporting
confidence: 49%
“…Email: jswang@uga.edu Food Additives & Contaminants: Part A, 2015http://dx.doi.org/10.1080/19440049.2015 and inadequate storage conditions. AF contamination has been reported in maize, cassava, groundnuts and locally manufactured baby foods including baby soya and rice porridge (Williams et al 2004(Williams et al , 2010Kaaya & Eboku 2010;Kitya et al 2010).…”
Section: Please Scroll Down For Arti Clementioning
confidence: 99%
See 1 more Smart Citation
“…High fumonisin levels in animal feed cause the specific diseases equine leukoencephalomalacia and porcine pulmonary oedema, and a variety of other adverse effects in multiple animal species ranging from reduced weight gain and productivity to immunotoxicity (Wu and Munkvold, 2008). Recent research has associated human exposures to fumonisins in Africa with increased susceptibility to HIV (Williams et al, 2010).…”
mentioning
confidence: 99%
“…There was a positive relationship between the AF level of white flour samples and the risk of esophageal cancer in Iran. The humidity and temperature of silos were the most important determinants of AF contamination of white flour [65]. There are some reports about human immunodeficiency virus (HIV) transmission frequency being positively associated with maize consumption in Africa.…”
Section: Aflatoxins In Oesophageal Cancermentioning
confidence: 99%